Size and layout optimum design of frames with steel plate shear walls by metaheuristic optimization algorithms. (February 2023) - Saedi Daryan, Amir; Salari, Mohadeseh; Palizi, Soheil; Farhoudi, Neda
Abstract: Optimization of a structure refers to a design procedure that results in the most economical structure in terms of materials and sizing of sections. In structures with steel plate shear walls, finding the best layout of the walls in a frame is also of priority in designing a structure with the minimum weight. Finding the least weight of a structure while all design provisions according to codes and standards are satisfied is a challenging task that is hard to perform with the existing design methods. Metaheuristic optimization algorithms are robust computational tools used for solving complex problems, which are used widely in many engineering fields, especially structural engineering. This paper presents a viable approach for the optimal design of frames with steel plate shear walls by applying modified dolphin echolocation (DE) and Bat optimization algorithms. The goal is to minimize the structure's weight, defined as the algorithm's objective function. To this end, a section list of beams and columns is predefined, and the algorithm selects the member's section from this list. Besides finding the appropriate sections, the algorithm tries different layouts of placing the walls in each span simultaneously. After finishing the iterations, the algorithm finds the best sections with the best layout of walls in a frame according to the mentioned objective function. The results of both algorithms are compared at the end of the process. Modified DE illustrated better performance than the Bat algorithm. For medium- and high-rise structures, the modified DE proposes more optimal designs. However, in a low-rise structure, the exact design is determined by both algorithms.